PENGARUH KEPUASAN KERJA DAN KOMITMEN ORGANISASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) (Karyawan pada PT PP (Persero) Tbk Proyek Supermall Pakuwon Indah Surabaya) - INDAH PERTIWI, DWI (Jurnal Ilmu Manajemen (JIM), 2016)
Organizations in this day and age should always be prepared for the changes to meet the demands of the times. To be able to compete competitively with other organizations, organizations are required to have adaptive nature and sensitive to changes in their environment. It is intended that the organization could be a good organization. To support these objectives, the resources required are competitive. So it is with PT PP (Persero) Tbk Project Supermall Pakuwon Indah which always focuses on managing its human resources in order to prepare human resource competitive, dynamic and dedicated. Job satisfaction and organizational commitment has been a concern which is significant in the study of the world of work. This is due to a general recognition that these variables can be a major determinant of organizational performance and effectiveness. It is important to study the impact of employees satisfied with their jobs and committed to the organization. It is striped linear with corporate goals that can be achieved with good. The population in this study is the staff at PT PP (Persero) Tbk Pakuwon Supermall Surabaya Indah Surabaya project as many as 110 people. Using the techniques of non-probability sampling and measuring instruments used questionnaires with data analysis techniques using PLS. The results showed that the effect of job satisfaction on organizational citizenship behavior (OCB) did not significantly and negatively. Organization commitment to organizational citizenship behavior (OCB) is not significant and negative effect on job satisfaction and organizational commitment has no effectsimultaneously on organizationalcitizenship behavior (OCB). . Keywords:job satisfaction, organizational commitment, organizational citizenship behavior